Hubungan Pengetahuan Dengan Sikap Ibu dalam Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Pranggang Kabupaten Kediri - Triatmi Andri Yanuarini; Dwi Estuning Rahayu; Ekanana Prahitasari (Akademi Keperawatan Dharma Husada Kediri, 2014)
Exclusive breastfeeding is breast-feeding for 6 months without any additional liquid. According to Health Department of Kabupaten Kediri in 2013, the exclusive breastfeeding program’s achievement is 57.2%. The lowest or the worst achievement of exclusive breastfeeding in Kediri is in Public Health center of Pranggang, it is 5.4%. The purpose of this study is to identify and analyze the correlation between mother’s knowledge and attitude in giving exclusive breastfeeding at territorial of Public Health in Pranggang - Kediri. The method which used in this study was the correlation of analytical studies using cross-sectional approach. The population of this study were all 54 breastfeeding mothers of babies aged 0-6 months in Pranggang, Punjul and Sumber Agung. The sampling technique in this study was the probability sampling with cluster sampling method. The samples in this study were 48 respondents. The results of the 48 respondents, 36 people (75%) had good breastfeeding. Statistical analysis of the data using the Spearman Rank test with a significance level of 0,05 and df = 46, it is obtained (5,694) > t table (2,021). It shows that there is correlation between mother’s knowledge and attitude in giving exclusive breastfeeding for babies in age 0-6 months at territorial of Public Health in Pranggang. The writer hopes the midwifery will give motivation more to the mothers for giving exclusive breast-feeding. Key words: Knowledge, Mother’s Attitude, Exclusive breastfeeding